2009
DOI: 10.1007/s10971-008-1890-1
|View full text |Cite
|
Sign up to set email alerts
|

Modification of aluminum alkoxides with β-ketoesters: new insights into formation, structure and stability

Abstract: Pr) 2 (b-ketoesterate)] 2 derivatives are asymmetrically substituted dimers with one octahedrally and one tetrahedrally substituted aluminum atom, bridged by two isopropoxo groups, whereas the Al(b-ketoesterate) 3 derivatives are monomers with octahedrally coordinated aluminum. Transesterification as a possible side reaction was only observed at elevated temperatures for Al(tert-butyl acetoacetate) 3 in the presence of liberated iso-propanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 13 publications
4
50
0
Order By: Relevance
“…The enol form of MAEAA is stabilized by chelation with an alkoxide. Further, the reaction also results in the stoichiometric replacement of an alkoxy group (e.g., an iso ‐propoxy group from gallium (III) iso ‐propoxide) by a β‐ketoester ligand,23–25 as shown in Equation 2. The general reaction of an alkoxide with MAEAA is shown in Equation 3.…”
Section: Resultsmentioning
confidence: 99%
“…The enol form of MAEAA is stabilized by chelation with an alkoxide. Further, the reaction also results in the stoichiometric replacement of an alkoxy group (e.g., an iso ‐propoxy group from gallium (III) iso ‐propoxide) by a β‐ketoester ligand,23–25 as shown in Equation 2. The general reaction of an alkoxide with MAEAA is shown in Equation 3.…”
Section: Resultsmentioning
confidence: 99%
“…The number of hydrolysable alkoxo groups decreases and additional coordination sites at the metal centers are blocked as a consequence of chelation. It was reported that the rate of hydrolysis and the extent of cross-linking in the formed network are decreased as a result of chelation [32]. Kessler et al [33] stated that hydrolysis and polycondensation reactions of metal alkoxides facilitated by the chemical modification and their kinetics have no direct relation to the sol-gel transformation.…”
Section: Polymeric Solsmentioning
confidence: 99%
“…HCl [9]. It could not exhibit instant gel formation with the addition of one drop of distilled water-ethanol mixture.…”
Section: Nano-structured Zirconia By Sol-gel Techniquementioning
confidence: 93%
“…There are various reports on the synthesis of nano-zirconia such as precipitation, hydrothermal synthesis, thermal decomposition and sol-gel technology, but sol-gel method is more advantageous because of its accomplishment with high purity, uniformity and homogeneity at lower sintering temperatures [8]. Being excessively hygroscopic in nature, obtaining nano-crystallites of ZrO 2 from zirconium alkoxides using the well-established sol-gel technology requires considerable attention and care because precipitation dominates over gelation [9]. Therefore, the moisture sensitivity of zirconium alkoxides could be retarded by substituting hydrolysable alkoxy groups with chelating ligands as modifiers [8,10,11].…”
Section: Introductionmentioning
confidence: 99%